Future scenarios for the US-Russian competition in the Caspian Sea region (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The Caspian Sea region is one of the oldest oil-producing regions in the world, and an increasingly important source in the global energy market. The Caspian Sea region receives special attention from experts and analysts in the field of international relations. the region at various political, security and economic levels. And this was confirmed by Stephen Kells, an American specialist and researcher, who said: “The Central Asia and Caucasus region is turning into a hotbed of international conflict that will make it one of the hot spots in the world, and that the United States of America has been carrying out a strong undeclared campaign for some time aimed at controlling Decisive on the Caspian Sea, and so do Russia and Iran and other regional powers, these fierce competitions made the region of Central Asia and the Caucasus the newest global arena for the policies of the great powers, "and although Russia represents one of the countries bordering the Caspian Sea, However, the researcher will study the Russian policy towards the Caspian Sea within the purification of international competition in the Caspian Sea, not the regional one, due to what it possesses Russia's prestige at the international level. It competes with the United States of America in a region that is no longer traditionally a vital area for the global interests of the United States of America, to become, due to its wealth, a geostrategic axis and a geopolitical heart in the map of American interests, which intensified the American-Russian competition over the Caspian Sea region, which has become one of the main drivers of the path of international and regional competition. In the twenty-first century